Web-Based Child Growth and Development Monitoring (Case Study: PKD Karangkemojing) - Imam Fadlilah, Nuzul; Saifudin, Saifudin; Widayanto, Aprih; Hellyana, Corie Mei (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
Children's nutritional health is a crucial factor in their growth and development. Regular monitoring of nutrition is essential for detecting and preventing dietary issues. This study aims to develop a web-based application for monitoring children's nutrition at the Village Health Center (PKD) in Karangkemojing Village. The methodology employed is the System Development Life Cycle (SDLC) approach, involving analysis, design, implementation, and evaluation. This web-based application allows health workers and parents to monitor children's nutritional status regularly through data on weight, height, and other nutrition indicators. It is expected that this application will enhance the efficiency of Posyandu cadres in monitoring children's nutrition. Additionally, the application facilitates access to nutritional information for health workers and parents while supporting decision-making regarding dietary interventions. The utilization of this application is anticipated to serve as a model for other regions in improving the quality of children's health services at the village level.